What Works in Youth Employment Policy? - Hahn, Andrew; Lerman, Robert (Washington D.C: National Planning Association, 1985)
The research reviewed by the authors demonstrates clearly that the most important factor causing persistent, concentrated youth unemployment is lack of basic educational skills. A national test revealed that 56 percent of black youth and 44 percent of Hispanic youth were functionally illiterate, compared to only 13 percent of youth overall
Includes bibliographic references
rpm 21/02/2018
Loans
Keywords: Employment; Employment Policy; Youth Employment